La prolifération des ordinateurs personnels dans l’entreprise : une autre étape - Gagnon, Marc (Assurances, 1984)
The author describes briefly what a company computer can do, with the necessary qualified personnel. In contrast, he shows how personal computers can be used to advantage. This is a straight-forward list of uses, giving a good idea of what a company computer as well as a personal computer can do for a firm which is prepared to make the necessary investment.